Implementation of Multimodal Assessments to Address Public Speaking Anxiety Among College Students - Mun Kuen, Wang; Wai Yie, Leong (INTI International University, 2025)
The ability to deliver oral presentations has been widely recognizable as one of the most essential skills in higher education and the workplace. This skill plays a vital role in securing a job for most fresh graduates. This study examines the implementation of multimodal assessments, incorporating various digital and interactive evaluation methods in higher education to address public speaking anxiety (PSA). Drawing from a case study, the study analyzes the effectiveness of integrating virtual reality (VR) and artificial intelligence (AI)-driven speech analysis in mitigating PSA. The findings highlight that multimodal approaches significantly decrease the anxiety level and build confidence through personalized feedback and track progress over time. A comparative analysis of traditional and multimodal assessment methods highlighting key differences in anxiety reduction, engagement, and overall speaking proficiency. The results demonstrate that multimodal assessments strategically improve students' speaking skills, as indicated by biometric and performance-based metrics